Land and property taxation in the Baltic States - Viktor Trasberg (European Regional Science Association (ERSA), 2003)
The paper is focused on developments of land taxation in the Baltic States during the last decade. In this period tax and budgeting reforms became an integral part of reform process in these countries. Devolution of government functions to the local level means more autonomous decision-making by sub-national governments, thereby also suggesting autonomous powers to raise revenue. The land tax clearly stands out as possibly one of the most important among several revenue sources collected mainly by the local governments. Together with land privatization and establishing of land markets, the Baltic governments are becoming more interested in the prospect of using that tax as a powerful instrument for revenue collection, which allows provide more public services. Presently, however, land tax systems do not allow local governments to make use of them as important raisers of revenue. Baltic countries are still far from designing efficient land taxation mechanisms. The most pressing list of problems already includes fundamental issues as proper land valuation, stimulating efficient use of land and poor tax administering. Also it should be stressed that land taxation is emotionally sensitive issue. Land reforms in the Baltic States introduced millions of new landowners. Many of these new landowners are likely to resist any changes in taxation of their property. The impact of land tax can also be important in steering regional development. Municipalities' strategy to design land (property) tax systems or rates for different parcels of land may cause population movements described by Tiebout. Therefore efficient land taxation systems should strengthen tax capacity of municipal governments and the optimal development of land use over time.
Keywords: 330